2022
DOI: 10.1002/anie.202210258
|View full text |Cite
|
Sign up to set email alerts
|

Inside Back Cover: Ultrathin Covalent Organic Framework Anchored on Graphene for Enhanced Organic Pollutant Removal (Angew. Chem. Int. Ed. 35/2022)

Abstract: An ultrathin covalent organic framework (COF) was constructed homogeneously on the surface of a graphene template via a facile hydrothermal method, as reported by Freddy Kleitz and co‐workers in their Research Article (e202206564). Benefitting from the maximum exposure of active sites and sufficient interaction with target water pollutants, the ultrathin COF could effectively shorten the equilibrium time and increase the adsorption capacity for the removal of organic dyes with various sizes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…Additionally, Kleitz et al have also successfully fabricated an ultralight anthraquinone-based COF/graphene aerogel (CGA) via a hydrothermal approach, in which ultrathin 2D COFs were uniformly grown on the surface of the graphene template. 198 In addition to graphene, other materials such as MoS 2 , MXene, CNTs, etc., have also been used to compound with 2DPs. 97,132,199 For instance, Wang et al reported the rational design and optimal synthesis of the electronically coupled semiconducting 2DP/MoS 2 heterostructures, successfully achieving the direct exfoliation of high crystallinity TIIP 2DP films condensed by pyrene and thienoisoindigo moieties down to a few nanometers (Fig.…”
Section: Heterostructures and Hybridsmentioning
confidence: 99%
“…Additionally, Kleitz et al have also successfully fabricated an ultralight anthraquinone-based COF/graphene aerogel (CGA) via a hydrothermal approach, in which ultrathin 2D COFs were uniformly grown on the surface of the graphene template. 198 In addition to graphene, other materials such as MoS 2 , MXene, CNTs, etc., have also been used to compound with 2DPs. 97,132,199 For instance, Wang et al reported the rational design and optimal synthesis of the electronically coupled semiconducting 2DP/MoS 2 heterostructures, successfully achieving the direct exfoliation of high crystallinity TIIP 2DP films condensed by pyrene and thienoisoindigo moieties down to a few nanometers (Fig.…”
Section: Heterostructures and Hybridsmentioning
confidence: 99%
“…Therefore, it can be concluded that the adsorption behavior of the two COFs on dyes aligns more closely with the pseudo-second-order kinetic model, suggesting a predominantly chemisorption mechanism. 37,38 To determine the maximum adsorption capacity of COFs for dyes and further investigate their adsorption thermodynamic behaviors, the adsorption thermodynamic experimental procedure 39 was as follows: under the conditions of constant adsorption time (180 mins), adsorbent mass (1 mg), and dye solution volume (20 mL), adsorption systems were constructed with initial MG concentrations of 25,30,35,40,50,60,80, and 100 mg L À1 , and ST concentrations of 10,20,25,35,45,60,80, and 100 mg L À1 , respectively. Similar to the adsorption kinetic experiments, the UV-Vis spectra corresponding to the above adsorption systems were collected, and then plots of q e versus equilibrium concentration (c e ) of YCOF1 and YCOF2 can be created (Fig.…”
Section: Dye Adsorptionmentioning
confidence: 99%
“…The exceptional chemical structure of graphene gives rise to its remarkable properties. Graphene possesses a theoretical specific surface area of 2630 m 2 g, [67] along with high mechanical strength (rupture strength of 42 N/m and Young's modulus of ≈1 TPa), [68][69][70][71][72] superfast electron mobility at low temperature [28,29,33,[37][38][39][40][41][42][43][44][45][46][47][48] (over 200 000 cm 2 V −1 s −1 ), [73] and outstanding thermal conductivity at room temperature (≈5000 W mK −1 ). [74] Owing to these unique physical and chemical properties, graphene exhibits vast potential for applications in electronic devices, [75] energy conversion, storage, [76][77][78] sensors, biotechnology, [79] environmental management, [42] and other fields.…”
Section: Graphenementioning
confidence: 99%